Catalytic deoxygenation of waste cooking oil for sustainable bio-jet fuel: A comparative study of Ni-Co/SBA-15 and Ni-Co/SBA-15-SH catalysts - Razak, Noor Azira Abdul; Taufiq-Yap, Yun Hin; Derawi, Darfizzi (Elsevier B.V., 2024)
This study focuses on the sustainable production of bio-jet fuel through the catalytic deoxygenation of waste cooking oil. The properties of two distinct catalysts at different Ni and Co loading (5 and 10 wt%), 5Ni5Co/SBA-15, 5Ni10Co/SBA-15, 10Ni5Co/SBA-15, 5Ni5Co/SBA-15-SH, 5Ni5Co/SBA-15-SH, and 10Ni5Co/SBA-15-SH were explored. It was observed that the functionalization of SBA-15 with silane (-SH addition) has successfully maintained the porous hexagonal structure, which is proven in the XRD and HRTEM analysis. Indeed, the presence of -SH in the bimetallic catalysts has contributed to increased surface area and pore size, as observed in the 5Ni5Co/SBA-15-SH catalyst. It was revealed that the bimetallic catalysts with 10 wt% of Ni and Co were not favorable as high metal content possibly blocked the porous support, reducing the active sites of the catalysts and decreasing deoxygenation activity. Indeed, the 5Ni5Co/SBA-15-SH catalyst showed superior performance of deoxygenation activity by producing 80 % of yield with 92 % of bio-jet selectivity, owing to the porous properties of the catalyst, which exhibits a substantial surface area (509 m2/g) and a significant pore size (4.4 nm). Furthermore, adding silane has successfully increased the acidic strength of the catalyst and promoted an efficient deoxygenation reaction. The result revealed that the wt% of metal loading and the functionalization of SBA-15 with silane has successfully improved the catalytic performance, leading to an efficient deoxygenation activity.